2014
DOI: 10.1007/s10773-014-2342-z
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational Dust Collapse in f (R) Gravity

Abstract: This paper is devoted to investigate gravitational collapse of dust in metric f (R) gravity. We take FRW metric for the interior region while the Schwarzchild spacetime is considered for the exterior region of a star. The junction conditions have been derived to match interior and exterior spacetimes. The assumption of constant scalar curvature is used to find a solution of field equations. Gravitational mass is found by using the junction conditions. It is concluded that the constant curvature term f (R 0 ) p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 92 publications
1
9
0
Order By: Relevance
“…Using junction conditions, Sharif and Kausar [10] have investigated the gravitational perfect fluid collapse in f (R) gravity. Recently, the spherically symmetric gravitational dust collapse using junction conditions in f (R) gravity has been discussed by Farasat et al [11].…”
Section: Introductionmentioning
confidence: 99%
“…Using junction conditions, Sharif and Kausar [10] have investigated the gravitational perfect fluid collapse in f (R) gravity. Recently, the spherically symmetric gravitational dust collapse using junction conditions in f (R) gravity has been discussed by Farasat et al [11].…”
Section: Introductionmentioning
confidence: 99%
“…The instability and anti-evaporation of Reissner-Nordström BHs have been explored in the modified f (R) gravity [45]. The inhomogeneous dust as well perfect fluid collapse with the geodesic flow condition in 4D have been explored in [46,47]. It has been remarked that f (R) with constant scalar curvature would appear as an alternative to the cosmological constant.…”
Section: Introductionmentioning
confidence: 99%
“…Sharif and Kausar [10] studied the spherically symmetric perfect fluid gravitational collapse in the f(R) theory of gravity. Farasat et al [11] investigated collapse with dust in the f(R) theory of gravity. They concluded that f (R 0 ) slows the collapse.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of research papers have been written to investigate gravitational collapse in extended theories of gravity [1][2][3][4][5][6][7][8][9][10][11][12]. It is shown that the further one goes from general relativity, there is a greater chance of naked singularity [4].…”
Section: Introductionmentioning
confidence: 99%